Healthcare Services Use and Satisfaction Among Iraqi and Syrian Refugees in San Diego: A Qualitative Study - Nissma Bencheikh; Omar Barakat; Ariana Khayamian; Lana Bridi; Nour Makarem; Tala Al-Rousan (Journal of Immigrant and Minority Health, 2026)
Abstract Arabic-speaking refugees in the United States face an elevated burden of chronic disease yet encounter significant barriers to care, and little research has examined their experiences in the U.S. primary care system. This study characterizes the patient experiences of Syrian and Iraqi refugees in San Diego to identify factors that enhance or hinder healthcare integration and satisfaction. Semi-structured interviews lasting 30 to 90 min were conducted in Arabic with 109 Syrian and Iraqi refugees residing in San Diego with a confirmed diagnosis of hypertension. Interviews were transcribed, translated, and analyzed using inductive thematic analysis. The Warwick Patient Experience Framework (WaPEF) guided the development of the interview guide and the organization of themes. Seven themes were identified across four WaPEF categories. Regarding service responsiveness, participants preferred providers who were perceived as sharing their language or cultural background, which facilitated trust and comfort. Within lived experience, comparisons with healthcare in participants’ home countries shaped expectations of U.S. care. Within the continuity of care and relationships, long wait times and limited appointment availability were major barriers that sometimes led to emergency department use, while proactive follow-up and trust facilitated consistent care. Within communication, language barriers and inconsistent interpreter services hindered care, while compassionate treatment strengthened the patient-provider bond. Language- and culture-concordant care, compassionate communication, and trusting patient-provider relationships facilitated positive healthcare experiences, while long wait times and inconsistent interpreter services remained key barriers. These findings identify opportunities to strengthen patient-centered care for Iraqi and Syrian refugee populations.